Tanggung jawab pendidikan menurut al-qur’an dan hadis - Asma; Yahiji, Kasim; Husain, Rahmin Thalib; Daud, Ilyas (Lebah, 2024)
In essence, the responsibility of education is a big and important responsibility. Because, in its operational setting, education is the provision of guidance, help and assistance from adults or people responsible for education to immature children. Basically, the responsibility for education starts from the family environment which starts from the child in the womb, then is born, gradually experiences growth and development, until the child becomes an adult who is aware of all his obligations, then the community, school, government and other institutions that have an interest. in education. This article describes the educational responsibilities of parents, teachers and society in order to guide and educate children so that they do not fall into hellfire by encouraging parents to pay attention to their families. So, parental education for the family can be a main and important concern in efforts to form people who believe and are devoted to God Almighty. Responsibility in terms of the Al-Qur'an and hadith explains that the family is responsible for each member of the family. This means that the family must play a role in realizing and making every member of their family into the people that Allah created them to be, namely as 'abdullahs/ servants who always dedicate themselves solely to Allah and become His caliphs in prospering the earth. So if the tasks leading to this direction are not carried out through family education, then Allah will threaten them with the torment of hellfire.